2021
DOI: 10.1038/s41598-021-95864-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of preterm very low birth weight infants admitted to an Italian tertiary center over an 11-year period

Abstract: Preterm very low birth weight infants (VLBWi) are known to be at greater risk of adverse neurodevelopmental outcome. Identifying early factors associated with outcome is essential in order to refer patients for early intervention. Few studies have investigated neurodevelopmental outcome in Italian VLBWi. The aim of our longitudinal study is to describe neurodevelopmental outcome at 24 months of corrected age in an eleven-year cohort of 502 Italian preterm VLBWi and to identify associations with outcome. At 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Our findings that both a low BW and being SGA are associated with NDI at both 2-and 5-years CA in BPD infants are in line with studies in the general preterm population, showing that intrauterine growth restriction contributes to the risk for having a lower BSID-III score [14,15]. This association probably results from abnormal brain development due to suboptimal environmental conditions during pregnancy such as hypoxemia, reduced blood flow, and malnutrition [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings that both a low BW and being SGA are associated with NDI at both 2-and 5-years CA in BPD infants are in line with studies in the general preterm population, showing that intrauterine growth restriction contributes to the risk for having a lower BSID-III score [14,15]. This association probably results from abnormal brain development due to suboptimal environmental conditions during pregnancy such as hypoxemia, reduced blood flow, and malnutrition [16].…”
Section: Discussionsupporting
confidence: 90%
“…Male preterm infants with BPD had a three-fold increased risk for NDI at 5-years CA, compared to their female peers. In an Italian cohort study, a comparable increased risk for male infants was seen at 2-years CA [14]. Gender differences in neurodevelopmental outcomes have been described before and may be caused by unmeasured biological variables likely to be caused by genetic and hormonal factors [17].…”
Section: Discussionmentioning
confidence: 90%
“…Study also proved that the LBW, with premature birth (< 37 week), intrauterine growth restriction (IUGR) and other genetic factors may develop cardiovascular and renal diseases 41 . Premature birth and LBW infants are on higher risk of developing genetic congenital outcome 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Preterm born infants are at a higher risk for adverse neurodevelopmental outcomes at 2 years of age [ 28 ], school age and during adolescence [ 29 , 30 ] compared to infants born at term. Studies examining prolonged apnea, as occurs during apnea of prematurity, have suggested that the resultant hypoxia is associated with an increased risk for neurodevelopmental impairment [ 5 , 31 ].…”
Section: Discussionmentioning
confidence: 99%